2011
DOI: 10.1002/pola.24609
|View full text |Cite
|
Sign up to set email alerts
|

Separation of ethylene‐propylene copolymers and ethylene‐propylene‐diene terpolymers using high‐temperature interactive liquid chromatography

Abstract: Ethylene‐propylene‐diene terpolymers (EPDM) are generally amorphous and, therefore, do not crystallize from solution. Consequently, fractionation techniques based on crystallization, such as crystallization analysis fractionation or temperature rising elution fractionation, cannot be used to analyze their chemical composition distribution. Moreover, no suitable chromatographic system was known, which would enable to separate them according to their chemical composition. In this study, two different sorbent/sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
(15 reference statements)
1
24
0
Order By: Relevance
“…Experiments confirmed that the molar mass or long chain branching in the above-mentioned samples [166] does not influence the HPLC separation. Independence of the elution volumes on the molar mass >15-20 kg/mol was also found for PE [164] and EP, EB, EO and ethylene/1-decene copolymers [161].…”
Section: Polyolefinssupporting
confidence: 78%
See 1 more Smart Citation
“…Experiments confirmed that the molar mass or long chain branching in the above-mentioned samples [166] does not influence the HPLC separation. Independence of the elution volumes on the molar mass >15-20 kg/mol was also found for PE [164] and EP, EB, EO and ethylene/1-decene copolymers [161].…”
Section: Polyolefinssupporting
confidence: 78%
“…Macko et al demonstrated the usefulness of the approach for EPC [164] and copolymers of propylene with different tacticities [165]. Moreover, terpolymers of ethylene, propylene and a diene monomer (EPDM) were separated [166]. It was found that both comonomers, ethylene and diene, are adsorbed.…”
Section: Polyolefinsmentioning
confidence: 96%
“…TCB has been used to desorb polyolefins from Hypercarb™ and other carbonaceous sorbents at 140 or 160°C. It is known that temperature can alter the extent of adsorption of synthetic polymers on a solvent/sorbent interface .…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of the development of the sorbent/solvent systems for selective chromatographic separation of polyolefins were summarized recently by Macko et al . Complete reversible adsorption of polyethylene (PE) and polypropylene (PP) on porous graphite (Hypercarb™) using a solvent gradient consisting of 1‐decanol and 1,2,4‐trichlorobenzene (TCB) at temperatures as high as 160°C was described in series of papers . Various other carbon sorbents have been applied for LC separations of various substances , however, not for polyolefins.…”
Section: Introductionmentioning
confidence: 99%
“…4). 1-decanol was chosen as adsorption promoting liquid as the retention of HDPE is larger in comparison with other solvents like 2-octanol and 2-ethyl-1-hexanol and furthermore dissolution was good in 1-decanol [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]81] and TCB, which is the solvent commonly used in SEC of polyolefins, was applied as desorption promoting liquid. Fig.…”
Section: Hplc Of Polyethylene and Ethylene/1-butene Copolymersmentioning
confidence: 99%